Towards the Development of Human Capital: Preliminary Results on a Study on Well-being Among Tertiary Students in Melaka, Malaysia - Mohd Amin, Suhaida; Mohd Rafien, Nor Shahrina; Md Taib, Norraeffa; Othman, Azhana; Ibrahim, Siti Nurulhuda (Information Management and Business Review, 2024)
Economic development is intimately linked to human resource development. People who can improve themselves fast and efficiently successfully deal with life’s problems and challenges, including those who are in tertiary education. Therefore, their stress level is an indicator of the well-being of our future leaders. This study investigates the various factors that can affect tertiary students’ well-being. This preliminary research involves collecting data from higher education institutions in Melaka, with 191 completed responses. The findings were analyzed using frequencies, percentages, mean, standard deviation, and correlation. Findings show that 62.8% of respondents experience low stress, while 37.2% report high stress. Key stressors include time pressure, academic dissatisfaction, and subject matter issues, with financial and social factors also contributing to stress levels. However, relationships and environmental factors appear to have a lesser impact on their stress levels. Based on the correlation coefficient, stress level (dependent variable) does not relate to single variables. Most variables have a moderate correlation with the other variables. The study’s findings show that tertiary students in Melaka do not experience alarmingly high levels of stress, but several factors do affect them. Therefore, well-being must be prioritized to ensure the best human capital can be created, as it represents future leaders and a skilled workforce. Recommendations are made for policy adjustments to address stress factors, providing human capital development for sustained national progress.